2012
DOI: 10.1002/anie.201203308
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic NMR Shifts for Saddle‐Shaped Five‐Coordinate Iron(III) Porphyrin Complexes with Intermediate‐Spin Structure

Abstract: Calculable results: Complex density functional calculations and spin distribution analyses have been performed for planar and saddled iron(III) porphyrin complexes (see picture). The spin populations and the extent of the interactions between the metal and the porphyrin orbitals were determined, which can explain the large change of meso-carbon atom chemical shifts observed for different porphyrin ligands

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…An interesting application of pNMR spectroscopy was recently reported by Chen & Chen (C&C) in a study of saddleshaped five-coordinate Fe(II) porphyrin complexes with intermediatespin structure. 94 Table 10 collects our calculated and the experimental 13 C chemical shifts determined by C&C of a tetraphenylporphyrin-iron(III) chloride complex in two conformations and two different spin states. A table listing the chemical shift differences of the a and b carbon chemical shifts relative to that of the meso carbon can be found in the ESI.…”
Section: Relativistic Effects and Finite-nucleus Corrections: Nickelo...mentioning
confidence: 99%
“…An interesting application of pNMR spectroscopy was recently reported by Chen & Chen (C&C) in a study of saddleshaped five-coordinate Fe(II) porphyrin complexes with intermediatespin structure. 94 Table 10 collects our calculated and the experimental 13 C chemical shifts determined by C&C of a tetraphenylporphyrin-iron(III) chloride complex in two conformations and two different spin states. A table listing the chemical shift differences of the a and b carbon chemical shifts relative to that of the meso carbon can be found in the ESI.…”
Section: Relativistic Effects and Finite-nucleus Corrections: Nickelo...mentioning
confidence: 99%
“…The energy difference between these two states, ΔE( 3 A 2 − 1 A 1 ), decreases in order from Co(OETPP)I to Co(OETPP)Br and then Co(OETPP)Cl. These results can be rationalized through a molecular orbital energy level representation from DFT fragment orbital calculations 15,16 (Scheme 1), which coincides with the effects on the d z 2 orbital by axial ligands and on the a 2u orbital by the para substituent of the meso-phenyl groups (Table 1). The most electronegative axial ligand (Cl), lowering the d z 2 orbital in energy, and the best electron-donating ring macrocycle [OET(p-CH 3 )PP], raising the a 2u orbital in energy, result in the weakest antiferromagnetic coupling in the Co[OET(p-R)PP]X (R = CF 3 , H, CH 3 ; X = I, Br, Cl) complexes (i.e., the weakest bond formation), 17 which, in turn, will decrease the energy difference between the singlet and triplet states and induce a larger contribution from the ferromagnetic triplet excited state.…”
mentioning
confidence: 99%
“…The energy difference between these two states, Δ E ( 3 A 2 – 1 A 1 ), decreases in order from Co(OETPP)I to Co(OETPP)Br and then Co(OETPP)Cl. These results can be rationalized through a molecular orbital energy level representation from DFT fragment orbital calculations , (Scheme ), which coincides with the effects on the d z 2 orbital by axial ligands and on the a 2u orbital by the para substituent of the meso -phenyl groups (Table ).…”
mentioning
confidence: 99%
“…Our previous DFT studies have indicated that the Fe III (d z 2 , d x 2 À y 2 )-porphyrin (a 2u ) interactions in fivecoordinate saddled high-spin and intermediate-spin Fe III porphyrins are stronger than the planar d z 2 -a 2u interactions; in addition, greater saddling deformation is associated with stronger d x 2 À y 2 /d z 2 -a 2u interaction. [32,34] To understand how such saddle-induced orbital interactions accelerate OÀ O homolysis, we employed DFT calculations based on the ZORA-B3LYP/TZ2P//BP86-D3/TZP and ZORAÀ S12 g/ TZ2P//BP86-D3/TZP levels, including COSMO/CH 2 Cl 2 , implemented in the ADF program to examine the homolytic OÀ O bond cleavage of the 5-coordinate Fe III -OOR species to Fe IV -oxo species, via an OÀ O bond breaking transition state (i. e., 2 OM ! TS_2 OM !3 OM and 2 OE !TS_3 OE !3 OE ).…”
Section: Resultsmentioning
confidence: 99%
“…However, porphyrin a 2u interacts with the Fe III dz2 orbital only with C 4 v symmetry (five‐coordinate planar porphyrins) but interacts with the dz2 and dx2-y2 orbitals with C 2 v (or lower) symmetry (five‐coordinate saddled porphyrins). Our previous DFT studies have indicated that the Fe III (dz2 , dx2-y2 )‐porphyrin (a 2u ) interactions in five‐coordinate saddled high‐spin and intermediate‐spin Fe III porphyrins are stronger than the planar dz2 ‐a 2u interactions; in addition, greater saddling deformation is associated with stronger dx2-y2 /dz2 ‐a 2u interaction [32,34] …”
Section: Resultsmentioning
confidence: 99%